“The Heart of this People is in its right place”: The American Press and Private Charity in the United States during the Irish Famine - Hamera, Paweł (Text Matters: A Journal of Literature, Theory and Culture, 2018)
The potato blight that struck Ireland in 1845 led to ineffable suffering that sent shockwaves throughout the Anglosphere. The Irish Famine is deemed to be the first national calamity to attract extensive help and support from all around the world. Even though the Irish did not receive adequate support from the British government, their ordeal was mitigated by private charity. Without the donations from a great number of individuals, the death toll among the famished Irishmen and Irishwomen would have been definitely higher. The greatest and most generous amount of assistance came from the United States. In spite of the fact that the U.S. Congress did not decide to earmark any money for the support of famine-stricken Ireland, the horrors taking place in this part of the British Empire pulled at American citizens’ heartstrings and they contributed munificently to the help of the Irish people. Aiding Ireland was embraced by the American press, which, unlike major British newspapers, lauded private efforts to bring succour to the Irish. Such American newspapers as the Daily National Intelligencer, the New York Herald and the Liberator encouraged their readers to contribute to the relief of Ireland and applauded efforts to help the Irish. The aim of this essay is to argue that the American press, in general, played a significant role in encouraging private charity in the United States towards the Irish at the time of An Gorta Mór and, thus, helped to save many lives.